Портрет Мастера сквозь призму личной судьбы и судьбы социологии ГДР. Памяти профессора Хельмута Штайнера - Куценко, О. (Социология: теория, методы, маркетинг, 2009)
The article is dedicated Professor Helmut Steiner’s memory, an outstanding Eastern German Sociologist, intellectual, broad-minded person who is gone away 14 February 2009. Through a prism of H.Steiner’s personal life a complicate, dramatic, and, in fact, tragic (in its final stage after the German unification since the 1990s) history of forming and development of Sociology in the German Democratic Republic is revealed in some significant strokes. Sociology in GDR formed on the ruin of post-war split German society, intensively developed under high level of the society’s anti-fascist and socialist consolidation since the end of the 1950s, tested enormously strong ideological pressure from the side of the political system since the end of the 1960s, has more or less coped with many barriers and produced the original scientific culture as well as research outcomes picturing many deep tendencies of society development. In such a development there was especially significant a personal scientific, ethic and life position of the Sociologist, living for the science, whose life serves the highest values of vocation that cannot exist without critique of society.